2006
DOI: 10.1037/0893-3200.20.2.292
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of internalizing, externalizing, and grades for children who have and have not experienced their parents' divorce or separation.

Abstract: This study examined whether the occurrence and timing of parental separation or divorce was related to trajectories of academic grades and mother-and teacher-reported internalizing and externalizing problems. The authors used hierarchical linear models to estimate trajectories for children who did and did not experience their parents' divorce or separation in kindergarten through 10th grade (N = 194). A novel approach to analyzing the timing of divorce/separation was adopted, and trajectories were estimated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
98
2
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(128 citation statements)
references
References 28 publications
10
98
2
14
Order By: Relevance
“…2006). Our finding that there were few and relatively weak ‘child effects’ is in line with previous UK research that tends to find stronger parent‐to‐child than child‐to‐parent effects, particularly with regard to externalizing behaviour (Steele et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2006). Our finding that there were few and relatively weak ‘child effects’ is in line with previous UK research that tends to find stronger parent‐to‐child than child‐to‐parent effects, particularly with regard to externalizing behaviour (Steele et al .…”
Section: Discussionmentioning
confidence: 99%
“…The timing of parents' partnership transitions also appears to be important. For example, Lansford and colleagues (2006), following a sample of children from kindergarten through 10th grade, showed that parental divorce during elementary school was more negatively related to trajectories of children's internalizing and externalizing behaviour problems than was later divorce, whereas later divorce was more negatively related to children's school grades.…”
Section: Introductionmentioning
confidence: 99%
“…A literatura aponta que crianças de famílias divorciadas estão em risco de apresentar problemas de ajustamento 6,12,13 . A metanálise de Amato e Keith 5 mostra que crianças de pais divorciados, quando comparadas com crianças que vivem em famílias intactas, exibem indicadores de menor bem-estar, incluindo pior realização acadêmica, ajustamento psicológico, autoconceito, relações sociais e qualidade de relacionamento com o pai e a mãe.…”
Section: Introductionunclassified
“…Como outras situações familiares estressantes, o divórcio aumenta a probabilidade de pais e crianças evidenciarem mal-estar psicológico 1,2,5-7 . Reações adversas em vários níveis, assim como sintomas que são comuns nessa fase de transição, têm sido descritas nos mais variados estudos [6][7][8][9][10][11] .A literatura aponta que crianças de famílias divorciadas estão em risco de apresentar problemas de ajustamento 6,12,13 . A metanálise de Amato e Keith 5 mostra que crianças de pais divorciados, quando comparadas com crianças que vivem em famílias intactas, exibem indicadores de menor bem-estar, incluindo pior realização acadêmica, ajustamento psicológico, autoconceito, relações sociais e qualidade de relacionamento com o pai e a mãe.…”
unclassified
“…Apoiando-se nesta base explicativa, algumas evidên-cias de estudos longitudinais reportam que indivíduos que experienciaram a separação dos pais apresentam mais problemas de internalização e de externalização do que aqueles que nunca vivenciaram uma experiência de separação dos pais 46 .…”
Section: Problemas De Internalização E Externalização: Uma Perspectivunclassified